Analysis of organizational communication in improving the working climate of employees at Radio Maestro - Viannisa, Nadhifa; Wardiana Sjuchro, Dian; Yudhapramesti, Pandan (Universitas Ahmad Dahlan, 2025)
In the face of an era of media convergence and increasingly fierce competition, radio as a mass media continues to strive to remain relevant to its listeners this article highlights the important role of organizational communication in building a positive work climate at Radio Maestro Bandung. Through a qualitative approach, the research identifies effective communication practices such as open communication, ongoing training, and collaboration across social media platforms that support employee motivation and performance. Radio Maestro implements a positive attitude-based strategy in the recruitment process, competency development, as well as providing innovative challenges, despite the challenges of funding and digital media competition. Digital transformation is a key focus in their adaptation to media convergence, including upskilling employees, rebranding, and using platforms like TikTok to expand the reach of young audiences. Effective internal communication support and proactive management are key to success in this change process. Despite facing resistance to innovation, Radio Maestro remains committed to growing and strengthening its digital infrastructure for sustainability in an increasingly competitive media industry. As a result, a conducive “full heart” work culture is created, maintaining the relevance and adaptability of radio in the digital era. This research contributes to enriching the understanding of the strategic role of organizational communication in the process of digital media transformation, especially in local radio, and provides an overview of effective communication practices that can be replicated by other media in facing the era of convergence.